2022
DOI: 10.31584/jhsmr.2022910
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Radiation Dose in Computed Tomography Angiography before Transcatheter Aortic Valve Implantation

Abstract: Objective: To investigate the effective radiation dose and image quality of computed tomography angiography (CTA) before transcatheter aortic valve implantation (TAVI). Material and Methods: This study involved 65 participants, diagnosed with aortic valve stenosis and examined with CTA before TAVI. The total mAs, kVp, volume CT dose index (CTDIvol), and dose–length product (DLP) in each scanning phase were recorded. The effective dose was calculated by multiplying the DLP by the conversion coefficient (k=0.015… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…It has been reported that BMI had an effect on radiation dose due to an increase in tube voltage and current [23][24][25] . A significant correlation between BMI and DAP and RAK was also found in a previous study [23][24][25] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that BMI had an effect on radiation dose due to an increase in tube voltage and current [23][24][25] . A significant correlation between BMI and DAP and RAK was also found in a previous study [23][24][25] .…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that BMI had an effect on radiation dose due to an increase in tube voltage and current [23][24][25] . A significant correlation between BMI and DAP and RAK was also found in a previous study [23][24][25] . Since the BMI of patients from our unit A DSA was slightly higher than in the unit B DSA patients, this may have contributed to a higher radiation exposure in the unit A DSA patients.…”
Section: Discussionmentioning
confidence: 99%